Analysis Of Exhaust Volume Reduction In Oily Water Separator At SS. GOLDEN ISAIA - Muhammad Daffa; Hermanto, Andy; Kresno Yuntoro (Nama Jurnal Akmi, 2024)
An oily water separator is an auxiliary engine on board that is used to prevent the mixing of oil and water with density differences. The oily water separator is very important on board for the separation of the ship's bilges from oil content which can pollute the marine ecosystem. This matter also fulfills the requirements of MARPOL 73/78 Annex 1 when the researcher carried out a sea project on SS. Golden Isaia, The researcher found the abnormality of the oily water separator. There was a decrease in its discharge volume, in which the normal flow was 5 m 3 / hour, which became 1 m 3 / hour. The purpose of this research was to determine the causal factor of oily water separator decreasing discharge volume on SS. Golden Isaia, evaluate the impacts, and the efforts to solve this oily water separator decreasing discharge volume on SS. Golden Isaiah. This research uses a descriptive qualitative method by applying a fishbone diagram analysis model. Data collection techniques include observation, interviews, and literature review. The interviews involved three informants, there chief engineer the one responsible for all machinery on board, the second engineer whose responsible for the oily water separator, and oiler 1 as the second engineer's assistant. The research results conclude that the causal factors of oily water separator decreasing discharge volume such as the lack of pressure of the oily water separator feed pump, dirty process filter due to accumulated dirt, and unavailability of oily water separator maintenance history. The efforts to solve this oily water separator decrease discharge volume on SS. Golden Isaia such as the change of a feed pump set with the new one, cleaning the strainer and replacing the filter bag, and the documentation of repair and maintenance.